Risk analysis on password for web authentication - Omar, Mohd Hasbullah; Zainal Abidin, Ahmad Hisham; Abu Seman, Mohamad Amir (Universiti Utara Malaysia, 2006)
Web authentication nowadays very heavily depends on password.From online banking to email account access, the password has played an important role in authenticating users to the designated system.In controlling access to a system, trade-offs are made between security and convenience.If a resource is protected by a password, usually the security is increased and user will always found to be inconvenience to use the system.This research addresses the important of choosing the password for any designated systems by evaluating the risk of choosing the password.Three password schemes were analyze in order to find the best scheme for the system administrator to provide suitable advice to their users.The outcome of the research will hopefully guide users to choose a strong and reliable password for web access.